Understanding the New Stress Factors Affecting Teachers' Burnout: A Scoping Review - Thomas, Joby; Reyes, Marc Eric S. (Makara Human Behavior Studies in Asia, 2024)
The teaching profession is extremely vulnerable to burnout. The sudden outbreak of the COVID-19 pandemic posed new threats and changed the educational environment, the perceptions and the values of teachers. The traditional in-person learning approach was quickly replaced by distant online learning to continue education. As schools reopened, a new educational platform, the hybrid learning model, evolved by fusing the two learning models. The high expectations placed on teachers to swiftly adopt new teaching methods—often without the required resources or training—exacerbated their exhaustion. We conducted a scoping review to determine the new stress factors that cause teachers’ burnout, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 statement. A total of 27 studies were systematically reviewed, and we identified numerous stress factors that affect teachers’ burnout. These stressors increased the already existing difficulties, magnifying their detrimental impacts. The stress factors were categorized as organizational, individual, transactional, emotional, cultural, or digital. This review suggests additional research is needed to understand the prevalence of teacher burnout and the effects that these stressors have on teachers’ personal and professional lives over time. Despite these challenges, this study demonstrates the need for more in-depth analysis to develop means to reduce teachers’ burnout and support them in maintaining their professional lives.